2014
DOI: 10.1111/codi.12667
|View full text |Cite|
|
Sign up to set email alerts
|

Inter‐observer and intra‐observer variability in the diagnosis of dysplasia in patients with inflammatory bowel disease: correlation of pathological and endoscopic findings

Abstract: Dysplasia is reliably diagnosed by expert gastrointestinal pathologists but has poor correlation with an endoscopic diagnosis of dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…The accuracy of the overall differentiation described in our study (overall 62%, expert 68%, and nonexpert 58%) was similar to the accuracy observed in the study from Farraye where standard white light endoscopy was used (overall 65%, expert 75%, and nonexpert 56%) [25]. Although comparing the results of two image-based studies is not the optimal study approach, this suggests that the additional value of pCE in differentiating lesions encountered during IBD surveillance is smaller than previously perceived.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The accuracy of the overall differentiation described in our study (overall 62%, expert 68%, and nonexpert 58%) was similar to the accuracy observed in the study from Farraye where standard white light endoscopy was used (overall 65%, expert 75%, and nonexpert 56%) [25]. Although comparing the results of two image-based studies is not the optimal study approach, this suggests that the additional value of pCE in differentiating lesions encountered during IBD surveillance is smaller than previously perceived.…”
Section: Discussionsupporting
confidence: 87%
“…A recent study by Allende and colleagues looked at the correlation between endoscopic diagnosis and pathology and showed a poor correlation. In over half of the cases, dysplasia was seen histologically in which the endoscopic diagnosis was negative [25]. Although this study was performed from a pathological perspective, the poor correlation between endoscopy and pathology is comparable to our results and reflects the difficulties in making a diagnosis of lesions found during IBD surveillance colonoscopy solely based on the endoscopic image [26].…”
Section: Discussionsupporting
confidence: 65%
“…The lack of agreement in the grading of CCA was expected, as significant interobserver variability, particularly at the lower end of the dysplasia spectrum (NEG versus IND versus LGD), has been reported in IBD . Although the earlier study by Riddell et al .…”
Section: Discussionmentioning
confidence: 90%
“…suggested that good to modest interobserver agreement among pathologists could be achieved for the diagnosis of IBD‐related dysplasia, others have demonstrated that interobserver agreement is only fair for HGD (kappa = 0.54–0.61) and poor for LGD (kappa = 0.18–0.23) among both general and GI pathologists . Similarly, a high level of disagreement in the diagnosis of IND has been reported (kappa = 0.01–0.25) . Recognising that it would be difficult to establish objective criteria to diagnose and/or grade CCA in a consistent and reliable manner based on morphology alone, we believe that additional criteria should be sought.…”
Section: Discussionmentioning
confidence: 99%
“…This system consists of 4 categories-negative for dysplasia, IND, LGD, and high-grade dysplasia-with an overall fair and modest interobserver agreement for negative for dysplasia and high-grade dysplasia, and poorer agreement (higher variability) for LGD and IND. [97][98][99] The IND category is used when the epithelial changes cannot be classified as either negative or positive for dysplasia with certainty. For example, IND may be rendered when coexisting florid acute inflammation, lack of the surface epithelium for evaluation, or processing/technical issues preclude definitive assessment of the epithelial alterations.…”
Section: Terminologymentioning
confidence: 99%